2012
DOI: 10.5539/ass.v8n10p85
|View full text |Cite
|
Sign up to set email alerts
|

In-directness and Politeness in American English and Saudi Arabic Requests: A Cross-Cultural Comparison

Abstract: This article examines the notions of (in)directness and politeness in the speech act of requests among Saudi Arabic native speakers as compared to American English native speakers. To elicit data on the requestive strategies that the two groups employed, a randomly chosen group of 30 Saudi and American undergraduate students were given a discourse completion test that consisted of twelve written context-enriched situations. The results revealed that conventional indirectness was the most prevailing strategy em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
0
35
1
Order By: Relevance
“…This article contains a description of the language politeness of the public leaders in the act of speech in Facebook. Some previous research on language politeness in speech acts, among others, conducted by Anggraeni (2005), Manaf (2010) Purnomo (2011, Tawalbeh and Al-Oqaily (2012), Susanto (2014), Codreanu and Dust (2014), Vega and Azókar (2014), Manaf and Amir (2015), and Yazdanfar and Bonyadi (2016). The results of the study can be explained as follows.…”
Section: Introductionmentioning
confidence: 99%
“…This article contains a description of the language politeness of the public leaders in the act of speech in Facebook. Some previous research on language politeness in speech acts, among others, conducted by Anggraeni (2005), Manaf (2010) Purnomo (2011, Tawalbeh and Al-Oqaily (2012), Susanto (2014), Codreanu and Dust (2014), Vega and Azókar (2014), Manaf and Amir (2015), and Yazdanfar and Bonyadi (2016). The results of the study can be explained as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The study of politeness in speech acts in the last ten years is done by Anggraeni (2005), Manaf (2010), Purnomo (2011, Tawalbeh and Al-Oqaily (2012), Susanto (2014), Codreanu and Debu 2014), Vega and Azókar (2014), Manaf and Amir (2015), and Yazdanfar and Bonyadi (2016). The results of these studies can be explained as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The speech strategies of native speakers of Arabic and native speakers of English have been studied by Tawalbeh and Al-Oqaily (2012). Codreanu and Debu (2014) examined politeness strategies of speech acts in Romanian, English, and Hebrew.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some researchers studied about the Politeness strategies. The first, Tawalbeh & Al-Oqaily (2012), conducted a study on in-directness and politeness in American English and Saudi Arabic Request: A Cross Culture Comparison. They found that conventional indirectness was the most prevailing strategy employed by the American sample.…”
Section: Introductionmentioning
confidence: 99%